The Relevance of Gender Mainstreaming in Indonesia to Women's Rights in Islamic Law - Rossa Ilma Silfiah; Humiati Humiati (Faculty of Law Universitas Lampung, 2023)
Gender mainstreaming is a government effort in upholding women's rights, because women's rights are an inseparable part of human rights. Protection of human rights is a state guarantee which is given to its citizens as a manifestation of the objectives of the Pancasila legal state as stated in the Preamble to the 1945 Constitution of the Republic of Indonesia. In Indonesia, gender mainstreaming has been established through Presidential Instruction Number 9 of 2000 concerning the Implementation of Gender Mainstreaming (PUG) under construction. This study will focus on gender mainstreaming on the development in Indonesia and the development of justice and gender equality in Islamic studies. Protection of human rights is the main goal in the application of Islamic law, including the protection of women's rights that has always been a major topic in Islamic studies and gender. By using qualitative descriptive method, it will be easy to find Islamic ideas, social activities at the time of the Prophet about women's rights. If examined comprehensively, in pre-Islamic history, namely the period of ignorance, it was a period that greatly demeaned women. At that time, if a baby girl was born, she would be buried alive right away, or if she was allowed to live, she would suffer humiliation. The purpose of this study is to find a conclusion that emphasizes women's rights which have been neglected so far, even though the use of religious arguments often prevents women from obtaining their rights. So with this affirmation, it is hoped that it will be able to control violence against women which has often occurred. Through gender mainstreaming, development is to achieve gender equality and justice (KKG) through integrating the experiences, needs, aspirations of women and men into various policies and programs starting from the planning, budgeting, implementation, and monitoring stages.